Students’ Satisfaction on Training cum Workshop Programme on Thesis Writing and General Research Skill Development - Duwal, Bal Ram (Journal of Nepalese Business Studies, 2020)
Faculty of Management, Tribhuvan University's Master of Business Studies level is not fully based on a research course that's why for many students thesis writing task is being the first attempt in their academic life. This study aims to determine students' satisfaction with the training cum workshop programme on their thesis writing and general research skills development and to assess the model that determines general satisfaction with the programme. Results showed that the participants are only satisfied to some extent with the training cum workshop programme. It was discovered that students show their disagreement on time allocated for every session, about following the time schedule by resource persons, resource persons’ use of practical ways, examples, and exercises in the session. However, they felt the method of thesis format, American Psychological Association styles of citation, and referencing are useful and the programme is going to help them more productively in near future. The step-wise regression model has also been used to set the model. The fitted model has been found to be significant. The model adequacy test has also been performed which shows the data satisfied the assumption of multicollinearity, normality of residuals, and homoscedasticity while no outliers were identified. The study between trained students and non-trained students' perceptions after the completion of their dissertation work can be carried out by future research. Likewise, a longitudinal study before the programme and after the thesis work can be performed in this area too.